Venta Belgarum prehistoric, Roman, and post-Roman Winchester - Morris, Francis M. 1982-; Biddle, Martin 1937-; Dannel, Geoffrey; Greep, Stephen; Henig, Martin 1942- (Archaeopress Publishing, 2023)
"This is a detailed study of the archaeology of Roman Winchester, Venta Belgarum, a major town in the south of the province of Britannia, and its development from the regional (civitas) capital of the Iron Age people, the Belgae, who inhabited much of what is now central and southern Hampshire."
Keywords: Vor- und Frühgeschichte; Funde; Römerzeit; Ausgrabung; Winchester